Nocturnos - Pérez Granell, Laura, 1983- (Fantagraphics Books, Inc., 2025)
In Nocturnos, acclaimed Spanish artist Laura Pérez invites readers into the mysterious world of night. Through hauntingly beautiful vignettes--of lonely roads, strange dreams, and eerie forests--she explores the thin line between imagination and reality. Each scene captures the quiet magic, melancholy, and mystery that emerge after dark, when the ordinary world gives way to something deeper and unseen.